Transforming Islamic Education Methodology in Indonesia: Implementing Fazlur Rahman’s Ideas Through a Process-Oriented Approach - Hidayat, Ahmad; Basyir, Kunawi; Pradesa, Dedy (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2024)
This study departs from the gap in the implementation of Fazlur Rahman’s contemporary educational ideas in learning methods. This study offers a process skills approach as a learning method to fill the gap. The aim of this study is to describe the application of the process skills approach in contemporary Islamic education in Indonesia as a synthesis of the implementation of Rahman’s ideas. The research method is qualitative literature. Data sources refer to Rahman’s works, and literature of Islamic education in Indonesia. The study results show that The process skills approach as a learning method is relevant as an operationalization of Rahman’s idea of Islamic education reform. Through the process skills approach, students are encouraged to actively process knowledge and develop scientific attitudes. In the context of Indonesian Islamic education, the application of process skills can be a solution to the renewal of Islamic education in the aspect of learning methodology.